2005
DOI: 10.1093/schbul/sbi045
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts a Good Response to Cognitive Remediation Interventions?

Abstract: Cognitive remediation is a behavioral intervention designed to improve cognition in people who have suffered a decline in neuropsychological functioning. The application of cognitive remediation for people with schizophrenia has become increasingly popular. In this article we attempt to determine what factors moderate outcome in cognitive remediation. This issue is of primary concern, as the efficacy of treatments largely depends on the appropriate selection of individuals and treatment methodologies that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
163
3
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(182 citation statements)
references
References 32 publications
9
163
3
7
Order By: Relevance
“…4,6 Model 2 indicates that both cognition and, in particular, social cognition are relevant targets for intervention. Interventions at the cognitive level [36][37][38] could have an impact on both cognition and social cognition. Additionally, this model confirms that social cognition has unique relations to functional outcome over and above those explained by cognition.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Model 2 indicates that both cognition and, in particular, social cognition are relevant targets for intervention. Interventions at the cognitive level [36][37][38] could have an impact on both cognition and social cognition. Additionally, this model confirms that social cognition has unique relations to functional outcome over and above those explained by cognition.…”
Section: Discussionmentioning
confidence: 99%
“…First, given the lack of clear improvement in social behaviors, it may be possible to increase the strength of the training by having the person complete the attentional-shaping condition several times a week or for longer periods of time. It is important to determine the correct "dose" or intensity of the treatment that may lead to more consistent changes in social functioning (Brekke et al, 2007;Medalia and Richardson, 2005). Currently, we are enhancing the shaping intervention by adding more faces which will allow repeated administration of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies conducted vary considerably in outcome measures and training interventions. Overall, there is some evidence that even severe cognitive impairment at baseline does not preclude gains through cognitive remediation (Medalia & Richardson, 2005). A recent study has even reported stronger improvement for patients with lower baseline cognitive performance and symptom severity during a compensatory cognitive training intervention (Twamley, Burton, & Vella, 2011).…”
Section: Introductionmentioning
confidence: 99%